Analisis bibliometrik perkembangan publikasi authentic assessment pada database scopus 1991 - 2023 - Amin, Khoirul; Ni’mah, Zulfatun; Susanto, Ari (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. Authentic assessment implementation faces challenges due to teachers' limited understanding and the absence of suitable assessment tools, leading to an unfair evaluation of students' cognitive, affective, and psychomotor skills. This study aims to trace the evolution of authentic assessment. Research Methodology. This research employs bibliometric analysis with the keyword "authentic assessment". Data Analysis. The data consists of 1,140 selected documents from the Scopus Database published between 1991 and 2023. Data analysis utilized the R-Package software from the R Program. Results and Discussion. Publications on authentic assessment displayed varying growth from 1991 to 2020, followed by a significant decline from 2021 to 2023. Nationalities, institutions, citations, affiliations, and inter-institutional collaborations significantly influence authentic assessment publication trends. Currently, "assessment authentic learning" is a trending research topic, while future opportunities focus on "evaluation" and "leadership century." Conclusion and Recommendations. This bibliometric study reveals a trend in publications related to authentic assessment.The USA, Deakin University and Messick, Gikandi JW, Darling have had a major influence on authentic assessment research. Future research should involve other databases for a more comprehensive and in-depth results.